FEATURES OF EPILEPSY AND PAROXYSMAL STATES OF VETERANS OF COMBAT OPERATIONS IN THE LONG TERM SUFFERING HEAD INJURIES - A. A. Zuikova; V. V. Emelyanova (Эпилепсия и пароксизмальные состояния)
Abstract: recent studies have shown that post-traumatic epilepsy is a common consequence of traumatic brain injury in combat veterans. In our study, epileptic syndromes occurred in 82% of veterans with the consequences of craniocerebral injury and combat stress. In 46.3% of cases of paroxysmal states accompanied by the development of behavioral disorders in 40.8% of the cases - affective disorders. Paroxysmal activity has a disintegrating effect on the brain and led to the development of mental disorders. In 2.6% of cases, we observed a delayed manifestation of symptoms of combat stress and myocardial injury after 10 or more years after taking part in the fighting.